Effects of a daytime nap on the recognition of neutral and emotional memories - Anuck Sawangjit (2018)
Background: Memory can be facilitated by the emotional strength of encoded information. Offline consolidation during sleep (post-learning sleep, even as little as a nap,) also modulates declarative memory processing. Previous studies have investigated the influence of sleep, especially rapid eye movement (REM) sleep, on emotional memory facilitation in humans. However, the interaction between emotional valence asymmetry and nap-dependent memory consolidation is poorly understood. Objective: To investigate the effects of post-learning nap on the recognition of neutral and emotional memories. Method: Ten healthy male participants completed a study session involving 240 emotional (negative and positive stimuli with different arousal magnitudes) and neutral pictures of people, animals, objects, and landscapes. Participants were then immediately tested on the visual recognition performance, in which they need to make recognition judgments on a subset of previously seen ("old") pictures and intermixed unseen ("new") pictures containing similar emotional and semantic contents. Three hours after this initial baseline test, one-half of the participants obtained a 90-minute nap opportunity, recorded with electroencephalography (EEG), whereas the others remained awake. Participants were again tested on the remaining "old" and "new" pictures at 6 hours after learning session. Results: The results revealed a beneficial effect of delayed post-learning nap on the recognition of neutral declarative memory. The extent of neutral memory facilitation was negatively correlated with the amount of stages-2 NREM. Unlike previous studies, the recognition performance for negative emotional items with high arousal condition in the Nap group deteriorated across an offline time rich in stage-2 NREM sleep. However, both groups showed similar decrease in recognition accuracy for positive stimuli. Conclusion: Our findings suggest that declarative memories containing distinct emotional valence and arousal are consolidated differentially during wakefulness and sleep. Under certain conditions, a daytime nap rich in stage-2 NREM sleep may play an important role on these performance differences.